Side and time variability of intraepidermal nerve fiber density. (9th June 2015) - Lauria, Giuseppe; Dacci, Patrizia; Lombardi, Raffaella; Cazzato, Daniele; Porretta-Serapiglia, Carla; Taiana, Michela; Sassone, Jenny; Dalla Bella, Eleonora; Rinaldo, Sara; Lettieri, Christian; Eleopra, Roberto; Devigili, Grazia
<x xml:space="preserve">Abstract</x> Objective: To assess the right-to-left and short-term variability of intraepidermal nerve fiber density (IENFD) at the distal site of the leg. Methods: Patients with possible or probable small fiber neuropathy (SFN) and healthy volunteers (HVs) underwent skin biopsies at the right and left distal leg. A subgroup of participants underwent follow-up biopsies 20 days later. Biopsies were immunostained by polyclonal anti-protein gene product 9.5 antibodies, and IENFD was quantified in nonconsecutive sections following published guidelines by operators blinded to the participants' condition (diagnosis, side, and time of biopsy). Findings were referred to sex- and age-adjusted normative values. Results: Forty patients and 17 HVs underwent bilateral skin biopsies; 15 patients and 8 HVs underwent follow-up skin biopsies. Sural nerve and dorsal sural nerve conduction studies were normal in all participants. Interside IENFD did not differ both in patients (median 2.45 IENF/mm ± 1.45 SD right; 2.2 IENF/mm ± 1.32 SD left) and HVs (median 6.3 IENF/mm ± 2.81 right; 6.2 IENF/mm ± 2.3 SD left). The right-to-left correlation coefficients were excellent (Pearson 0.95 in SFN and 0.97 in HVs). The analysis of IENFD at 20-day follow-up biopsy showed no difference between sides in both groups and yielded excellent correlation coefficients. Conclusions: The diagnosis of SFN can be reliably ascertained by unilateral skin biopsy at the distal site of the leg, and IENFD is not expected to vary within 3 weeks.